2020
DOI: 10.1001/jamasurg.2019.4704
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cognitive Aids on Adherence to Best Practice in the Treatment of Deteriorating Surgical Patients

Abstract: IMPORTANCE Failure to rescue causes significant morbidity and mortality in the surgical population. Human error is often the underlying cause of failure to rescue. Human error can be reduced by the use of cognitive aids.OBJECTIVES To test the effectiveness of cognitive aids on adherence to best practice in the management of deteriorating postoperative surgical ward patients. DESIGN, SETTING, AND PARTICIPANTS Randomized clinical trial in a simulation setting. Surgical teams consisted of 1 surgeon and 2 nurses f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 46 publications
0
38
0
Order By: Relevance
“…The use of cognitive aids can also help the team in the critical management of the deteriorating patient, with one study in a simulation environment reporting a decreasing in the percentage of omitted critical management steps of 70% [48]. Besides cognitive aids, the use of checklists structuring responses to clinical deterioration has potential to improve patient care and outcomes, since the first responders on the efferent limb are frequently an assembly of available providers of care with limited experience in managing emergency situations [28].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of cognitive aids can also help the team in the critical management of the deteriorating patient, with one study in a simulation environment reporting a decreasing in the percentage of omitted critical management steps of 70% [48]. Besides cognitive aids, the use of checklists structuring responses to clinical deterioration has potential to improve patient care and outcomes, since the first responders on the efferent limb are frequently an assembly of available providers of care with limited experience in managing emergency situations [28].…”
Section: Resultsmentioning
confidence: 99%
“…Cognitive aids aim to improve communication, teamwork and leadership and the surgical safety culture and accelerate escalation of care and optimize resuscitation by lowering omitted management steps, and therefore have potential to reduce FTR [48]. Despite the potential benefit in implementing this strategy to reduce FTR, there is still not a widespread use in clinical practice [48]. in the management of common emergencies while escalation to rapid response teams occur [14].…”
Section: Efferent Limbmentioning
confidence: 99%
“…Research involving simulation supports the use of cognitive aids in anaesthesia, as well as in other fields of medicine [39–42]. Despite the increased focus on human factors in anaesthesia, and the known evidence supporting the use of cognitive aids to reduce slips, lapses and mistakes, cognitive aids were not included in four guidelines, and mentioned but not presented in an additional 15, totalling 19 of 26 (73%) [43].…”
Section: Discussionmentioning
confidence: 99%
“… 4 Albeit small, pre-intervention and post-intervention studies have reported mixed outcomes when escalating therapy in response to early warning signs. 9 , 16 Simulation studies have shown that the use of cognitive aids (similar to the ASOS-2 bedside guide) can decrease the omission of critical management steps, 17 with fewer critical errors. 18 Feedback on patient outcomes can reduce major adverse events following surgery.…”
Section: Discussionmentioning
confidence: 99%
“…However, approximately 30% of all deaths within 30 days of surgery occur after hospital discharge globally, 7 and we expect a higher proportion of patients to die following discharge in resource-limited environments. 4,25 The key learning points from this study are that future attempts to provide pragmatic interventions for surgical patients with physiological deterioration in a resource-limited environment will need to be codesigned by all local role players to ensure appropriate buy-in with the risk stratification strategy, teamwork necessary to implement the intervention, application of cognitive aids, 17 communication of risk within the team, 9 and feedback on outcomes and performance. 19 Implementation strategies for resource-limited environments must include the use of educational meetings, tailoring and practising inter ventions, leverage of local leaders, and provision of feedback to change health-care provider behaviour.…”
Section: Discussionmentioning
confidence: 99%